Residual weed control in cotton utilizing herbicide-coated fertilizer - Brock A. Dean; Charles W. Cahoon; Guy D. Collins; David L. Jordan; Zachary R. Taylor; Jacob C. Forehand; Jose S. de Sanctis; James H. Lee (Weed Technology, 2025)
An experiment was conducted in 2022 and 2023 near Rocky Mount and Clayton, NC, to evaluate residual herbicide-coated fertilizer for cotton tolerance and Palmer amaranth control. Treatments included acetochlor, atrazine, dimethenamid-P, diuron, flumioxazin, fluometuron, fluridone, fomesafen, linuron, metribuzin, pendimethalin, pyroxasulfone, pyroxasulfone + carfentrazone, S-metolachlor, and sulfentrazone. Each herbicide was individually coated on granular ammonium sulfate (AMS) and top-dressed at 321 kg ha−1 (67 kg N ha−1) onto 5- to 7-leaf cotton. The check plots received the equivalent rate of nonherbicide-treated AMS. Before top-dress, all plots (including the check) were treated with glyphosate and glufosinate to control previously emerged weeds. All herbicides except metribuzin resulted in transient cotton injury. Cotton response to metribuzin varied by year and location. In 2022, metribuzin caused 11% to 39% and 8% to 17% injury at the Clayton and Rocky Mount locations, respectively. In 2023, metribuzin caused 13% to 32% injury at Clayton and 73% to 84% injury at Rocky Mount. Pyroxasulfone (91%), pyroxasulfone + carfentrazone (89%), fomesafen (87%), fluridone (86%), flumioxazin (86%), and atrazine (85%) controlled Palmer amaranth ≥85%. Pendimethalin and fluometuron were the least effective treatments, resulting in 58% and 62% control, respectively. As anticipated, early season metribuzin injury translated into yield loss; plots treated with metribuzin yielded 640 kg ha−1 and were comparable to yields after linuron (790 kg ha−1) was used. These findings suggest that with the exception of metribuzin, residual herbicides coated onto AMS may be suitable and effective in cotton production, providing growers with additional modes of action for late-season control of multiple herbicide–resistant Palmer amaranth.